Applying a generic workflow modeling technique to production workflows - (:unkn) unknown (My University, 2005)
Workflow technology is emerging as an appropriate tool to manage production systems. It manages automation of production orders, information or tasks and passes them from one station to another, in a way that is governed by rules or procedures. Before these automated workflows could be implemented, it is necessary to apply some modeling methodology to capture, analyse and describe the flow of tasks in a production process. In this paper we present a generic modeling technique that can be applicable to all kinds of production workflows. We present relevant workflow design patterns, identify basic characteristics of production workflows, and discuss some issues that should be targeted during the modeling process. We also apply the proposed modeling technique to production workflows as an application example for automation of manufacturing processes of a plant producing prefabricated building components.
Keywords: Modeling of workflow; Production workflows